2013
DOI: 10.4322/rbcv.2014.013
|View full text |Cite
|
Sign up to set email alerts
|

Adição de betaína ao diluente leite em pó desnatado durante a conservação do sêmen do varrão a 10°C

Abstract: A betaína é um constituinte do plasma seminal humano, cuja baixa concentração tem sido relacionada à infertilidade, entretanto não há relatos sobre seus efeitos no sêmen suíno. O presente estudo teve como objetivo verificar os efeitos da adição de diferentes concentrações de betaína sobre espermatozoides suínos diluídos e conservados em leite em pó desnatado a 10°C por quatro dias. Foram analisados 56 ejaculados submetidos a quatro tratamentos: 1. Leite em pó desnatado (LPD); 2. LPD+1g betaína/100mL; 3. LPD+2g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In addition, when compared to fructose added to BTS and SMP, there was no statistical difference between the means of living cells between the two extenders. Araújo et al (2013) demonstrated that the SMP was a great extender for boar semen at lower temperature (10 °C), giving greater protection to sperm cells through higher rates of vitality.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, when compared to fructose added to BTS and SMP, there was no statistical difference between the means of living cells between the two extenders. Araújo et al (2013) demonstrated that the SMP was a great extender for boar semen at lower temperature (10 °C), giving greater protection to sperm cells through higher rates of vitality.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, milk has a buffering capacity, bactericidal action, and an adequate viscosity for the maintenance of spermatozoa in a liquid medium (CUNHA, 2002). This diluent has already been tested in protocols for freezing boar semen (TONIOLLI et al, 2001;ARAÚJO et al, 2013), making a potential diluent for the sêmen-cooling step.…”
Section: Introductionmentioning
confidence: 99%